Epigenetic regulation in dental pulp inflammation. (28th March 2016) - Hui, T; Wang, C; Chen, D; Zheng, L; Huang, D; Ye, L
Abstract : Dental caries, trauma, and other possible factors could lead to injury of the dental pulp. Dental infection could result in immune and inflammatory responses mediated by molecular and cellular events and tissue breakdown. The inflammatory response of dental pulp could be regulated by genetic and epigenetic events. Epigenetic modifications play a fundamental role in gene expression. The epigenetic events might play critical roles in the inflammatory process of dental pulp injury. Major epigenetic events include methylation and acetylation of histones and regulatory factors, DNA methylation, and small non‐coding RNAs. Infections and other environmental factors have profound effects on epigenetic modifications and trigger diseases. Despite growing evidences of literatures addressing the role of epigenetics in the field of medicine and biology, very little is known about the epigenetic pathways involved in dental pulp inflammation. This review summarized the current knowledge about epigenetic mechanisms during dental pulp inflammation. Progress in studies of epigenetic alterations during inflammatory response would provide opportunities for the development of efficient medications of epigenetic therapy for pulpitis.